Evaluation of MRI protocols for the assessment of lumbar facet joints after MR-guided focused ultrasound treatment. Issue 1 (December 2016) - Krug, Roland; Do, Loi; Rieke, Viola; Wilson, Mark; Saeed, Maythem
Abstract Background MR-guided focused ultrasound (MRgFUS) might be a very safe and effective minimally invasive technique to treat facet joint pain caused by arthritis and other degenerative changes. However, there are still safety concerns for this treatment and challenges regarding MR imaging and temperature mapping due to susceptibility effects between the bone and soft tissue near the joint, which has resulted in poor MR image quality. The goal of this research was to evaluate multiple magnetic resonance imaging (MRI) pulse sequences for characterizing ablated lumbar facet joint lesions created by high-intensity focused ultrasound (FUS) and compare the findings to histological tissue assessment. In particular, we investigated the use of T2-weighted MRI to assess treatment effects without contrast administration. Methods An IACUC approved study (n  = 6 pigs) was performed using a 3T widebore MRI system equipped with an MRgFUS system. Facet joints of the lumbar vertebra were ablated using 1-MHz frequency and multiple sonication energies (300–800 J). In addition to T2-weighted MRI for treatment planning, T1-, T2-, and T2*-weighted and perfusion MRI sequences were applied. Signal intensity ratios of the lesions were determined. Histopathology was used to characterize cellular changes. Results Ablation of the facet joint, using MRgFUS, was successful in all animals. T2-weighted images showed high signal intensity in the edematous facet joint and adjacent muscle, while delayed contrast-enhanced T1-weighted images showed an enhanced ring surrounding the target volume. T2*-weighted GRE images revealed inconsistent lesion visualization. Histopathology confirmed the presence of cellular coagulation (shrinkage), extracellular expansion (edema), and hemorrhage in the bone marrow. Conclusions MRgFUS provided sufficient precision and image quality for visualization and characterization of ablated facet joints directly after ablation. MRI may help in monitoring the efficacy of FUS ablation without contrast after treating patients with back pain.